Polyphenol composition of wine from the variety Cabernet Sauvignon - A. Serafimovska; B. Korunoska; G. Milanov; M. Taseska-Gjorgjijevski; D. Nedelkovski (My University, 2022)
Polyphenols and their derivatives are complex compounds that are responsible for the color and quality of red wines. The goal of the research was to determine the polyphenolic composition and its influence on the color and quality of the Cabernet Sauvignon variety. Wines obtained from Skopje, Ovce Pole and Gevgelija-Valandovo regions were investigated. In young wines, chemical analysis of total polyphenols, total anthocyanins, tint and color intensity was performed. The analyses were carried out by using spectrophotometric methods and standard chemical methods. With a higher content of total polyphenols (3385 mg/L EGA) and anthocyanins (978 mg/L), the wine from Skopje wine region was distinguished. The richest chemical composition has the wine from the Ovce Pole wine region with the highest content of alcohol (14.58 vol.%), dry extract (30.8 g/L) and total acids (5.8 g/L). The polyphenolic composition of the wines depends on a number of factors: the variety-clone, the substrate, the agro-technical and ampelotechnical measures, the yield, the degree of maturity, the health condition, the harvesting and transport and the terroir.
Keywords: vineyards, Cabernet Sauvignon, wine, polyphenols, anthocyanins